The Effect of Love of Money and Religiosity on Ethical Perceptions of Accounting Students - Pratiwi, Lifia; Junaidi, Junaidi (Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the effect of love of money and religiosity on the ethical perceptions of accounting students. This research method uses quantitative methods with a population of students from the accounting study program at Muhammadiyah University of Palopo. The sample used had 300 respondents. Data were measured using a numerical scale (numbers) and analyzed using statistical formulas and Amos software. The results of this study indicate that the variables "love of money" and "religiosity" have a positive effect on the ethical perceptions of accounting students.